Enhancement of renal function with ornipressin in a patient with decompensated cirrhosis. Issue 12 (December 1985) - Lenz, K; Druml, W; Kleinberger, G; Hörtnagl, H; Laggner, A; Schneeweiss, B; Deutsch, E
Abstract : An infusion with Ornipressin (8-ornithin vasopressin) in a patient with decompensated alcoholic liver cirrhosis increased urinary volume from 30 ml/h to 500 ml/h, creatinine clearance from 24 to 65 ml/min, and fractional sodium excretion from 0.86% to 11.1%. Free water clearance decreased from -10.2 ml/h to -26.2 ml/h and noradrenaline plasma concentrations dropped from 2.04 to 1.37 ng/ml. After stopping Ornipressin infusion all values returned to initial concentrations. Possible effects are an increase of renal blood flow secondary to an increase in arterial blood pressure, possibly potentiated by the vasodilatory effect of the fall in noradrenaline and/or angiotensin concentration.